2016
DOI: 10.1007/s00249-016-1167-5
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the antimicrobial peptide Protegrin-5 in a membrane-mimicking environment. Structural studies by high-resolution NMR spectroscopy

Abstract: Protegrin pore formation is believed to occur in a stepwise fashion that begins with a nonspecific peptide interaction with the negatively charged bacterial cell walls via hydrophobic and positively charged amphipathic surfaces. There are five known nature protegrins (PG1-PG5), and early studies of PG-1 (PDB ID:1PG1) shown that it could form antiparallel dimer in membrane mimicking environment which could be a first step for further oligomeric membrane pore formation. Later, we solved PG-2 (PDB ID:2MUH) and PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Solid-state NMR provided some evidence that protegrin may form β-barrels containing 8–10 monomers in NCCN parallel topology 25 (see Topology below). However, solution NMR in detergents showed NCCN antiparallel topology for protegrin-1 26 , protegrin-3 27 , and protegrin-5 28 . The same solid-state NMR study also showed that 75% of the hairpins have homodimerized N and C strands in an anionic membrane, implying that the β-barrel state is the dominant component of a heterogeneous mixture.…”
Section: Introductionmentioning
confidence: 96%
“…Solid-state NMR provided some evidence that protegrin may form β-barrels containing 8–10 monomers in NCCN parallel topology 25 (see Topology below). However, solution NMR in detergents showed NCCN antiparallel topology for protegrin-1 26 , protegrin-3 27 , and protegrin-5 28 . The same solid-state NMR study also showed that 75% of the hairpins have homodimerized N and C strands in an anionic membrane, implying that the β-barrel state is the dominant component of a heterogeneous mixture.…”
Section: Introductionmentioning
confidence: 96%
“…Whereas molecules whose interactions are with proteinaceous receptors can be made inefficient by one or a few changes in amino acid sequence, polypeptides that act by disrupting the lipid bilayer physicochemical properties are less likely to become inactivated by resistance (Rollins-Smith et al 2002). Indeed the amphipathic nature of AMPs has been found essential and can be achieved by helical (Sansom 1991;Bechinger 1997), cyclic (Cao et al 2018Laurencin et al 2018;Tsutsumi et al 2018;Zhao et al 2018), and/or β-sheet arrangements (Hong and Su 2011; Rautenbach et al 2016a, b;Sychev et al 2017;Usachev et al 2017). Thus the insights gained from the studies of cationic amphipathic antimicrobial peptides have stimulated the design of a number of small amphipathic molecules (Arnusch et al 2012;Ghosh et al 2014), pseudopeptides (Porter et al 2002;Patch and Barron 2003;Kuroda and DeGrado 2005;Violette et al 2006;Makovitzki et al 2008;Scott et al 2008;Rotem and Mor 2009;Palermo and Kuroda 2010;Laurencin et al 2018), and polymers (Rank et al 2017) with potent antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, molecules that specifically target proteinaceous receptors can be made inefficient by mutagenesis of one or a few sites, and it is much less likely that bacteria develop resistance to compounds whose primary target is the destruction of the physico-chemical properties of the lipid membrane [ 15 ]. Membrane-active peptides exhibit a wide range of structural features some being helical in their bilayer-associated state [ 16 , 17 ], others forming cyclic [ 18 , 19 , 20 , 21 ] and/or β-sheet arrangements [ 22 , 23 , 24 , 25 , 26 ]. Indeed, following the insights gained from the studies of cationic amphipathic antimicrobial peptides a number of small amphipathic molecules [ 27 , 28 ], pseudopeptides [ 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], and polymers [ 37 ] have been designed and investigated, and found to also exhibit potent antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%